Ultrafast hydrogen bond dynamics and partial electron transfer after photoexcitation of diethyl ester of 7-(diethylamino)-coumarin-3-phosphonic acid and its benzoxaphosphorin analog. Issue 15 (21st April 2015) - Wagner, M. S.; Ilieva, E. D.; Petkov, P. St.; Nikolova, R. D.; Kienberger, R.; Iglev, H.
<x xml:space="preserve">Abstract</x> The solvation dynamics after optical excitation of two phosphono-substituted coumarin derivatives dissolved in various solutions are studied by fluorescence up-conversion spectroscopy and quantum chemical simulations.